Optimizing COVID-19 surveillance in long-term care facilities: a modelling study - Smith, DRM; Duval, A; Pouwels, KB; Guillemot, D; Fernandes, J; Huynh, B-T; Temime, L; Opatowski, L; AP-HP/Universities/Inserm COVID-19 research collaboration (BMC, 2020)
Background: Long-term care facilities (LTCFs) are vulnerable to outbreaks of coronavirus disease 2019 (COVID-19). Timely epidemiological surveillance is essential for outbreak response, but is complicated by a high proportion of silent (non-symptomatic) infections and limited testing resources.